ANALYSIS OF FACTORS RELATED TO THE EVENT OF PRIMARY DYMENOROREA IN ADOLESCENT WOMEN IN SITINJAU LAUT DISTRICT - Puspita Sari; Lia Nurdini; Fefi Tri Yuzela; Fitria Eka Putri; Solihin Sayuti (International Journal Of Health Science, 2022)
Primary dysmenorrhea is menstrual pain that is found without obvious abnormalities of the genital organs. Primary dysmenorrhea often occurs in adolescent girls aged 10-14 years (early adolescence). Primary dysmenorrhea refers to pain without obvious pathological pelvic disease or menstrual pain with normal pelvic anatomy, usually beginning in adolescence after their ovulatory cycle has established. The purpose of this study was to determine the relationship between age of menarche, duration of menstruation and exercise habits in adolescent girls in Sitinjau Laut District. This research is a quantitative research with a cross sectional design. Data collection was carried out in March-April 2021. The research population was... Young Women with a research sample of 198 young women. Sampling was done by using proportional random sampling technique. This study consisted of the independent variable "age of menarche, duration of menstruation and exercise habits" and the dependent variable "primary dysmenorrhea". Data analysis using Chi-Square test. The incidence of primary dysmenorrhea in adolescent girls is 74.2%. Factors related to the incidence of primary dysmenorrhea in adolescent girls were age at menarche (P=0.000; 1.870; 95% CI 1.371-2.552) and length of menstruation (P=0.001; 0.720; 95% CI 0.635-0.817). And there is no relationship between exercise habits (P=0.720; 1.184 95% CI 1.012-1.835). There is a relationship between the age of menarche with the incidence of primary dysmenorrhea and the length of menstruation in adolescent girls in the District of Sitinjau Laut.